Afídeos e suas interações biológicas em áreas de vegetação natural e agrícolas : exemplo de sucesso nas invasões biológicas - Cunha, Suzan Beatriz Zambon da (2017)
The introduction of exotic species affects ecosystems world widely. Aphids (Hemiptera: Aphidoidea) are especially prone to be invasders by presenting characteristics as small sizes, assexual reproduction, and the capacity of involuntarialy invade distant regions, being transported together with their host plants. The main objective of this research was to make an inventory of exotic invasive aphids and also of their hosts, parasitoids and predators in both, natural vegetation and its agricultural surrounding areas. Samplings were carried out in the remaining Cerrado area at the Federal University of São Carlos campus, in the Ecological Station of Itirapina, and in The State Parks Campos do Jordão, Furnas do Bom Jesus, Porto Ferreira and Vassununga. Twelve hours of sampling were performed in each locality, in the rainy and dry seasons in the period between from April 2014 to March 2016. The aphids, possible predators and parasitoids were collected directly in the host plants and identified down to the lowest possible taxonomical level. A total of 7,875 aphids, 5,748 ninphs, 1,642 apterous adults and 485 winged adults over different host plants belongiong to 42 botanical families, distributed in 266 samples. In these samples 38 species of aphids and 50 species of host plants were found. The species Aphis spiraecola, Toxoptera aurantii and A. gossypii were the most abundant, respectively. Plants of the Asteraceae family were the preferred hosts of aphids. The largest number of host plants and highest species richness of aphids were obtained from teh State Park of Campos do Jordão. There were no visual differences in relation to the number of samples obtained in each seasonal period, and aphids were collected year round. Among the aphid/plant interactions observed, 43 are new associations. The emergence of the parasitoids Lysiphlebus testaceipes (Crensson, 1880) and Xenostigmus bifasciatus (Ashmead 1891) and of the hyperparasitoids Pachyneuron aphidis (Bouché, 1834), Syrphophagus sp. Ashmead and Euneura sopolis (Walker,1840) were obtained. We also obtained the uncommon emergence of a parasitoid of the Diapriidae family parasitizing the aphid Picturaphis vignaphyllus. Amonf predators were collected: siyrphíds, crysopíds and the coccinelíds Harmonia axyrids (Pallas, 1773), Hippodamia convergens (Guérin-Méneville, 1842) and Cycloneda sanguínea. In the surroundind agricultural areas aphids only occurred in sites of predominantly coffee culture, as in the State Park of Furnas do Bom Jesus. In the context of exotic species, we could see that among the 165 species of aphids occurring in Brazil, only 16% have their probable origin in the Neotropical region. The remaining species considered exotic are mainly originary from the Paleartic region (37%), being the import and trade of ornamental plants the mai responsible for the increasing entrance of exotic aphid species in Brazil until 2004. From this year onwards although imports continued to increase, the number of exotic aphids decreased due to greater control and efficacy in preventing entrance of exotic species in the country. The success of exotic aphids in Brazil can be partially attributed to global climate changes and to the degree of importance of host s to the Economy. Therefore researches and the presence of aphidologists at agricultural regions will be of great importance to the recording, early warning and actions regarding exotic invasive species.